IMPLEMENTASI PELAPORAN BAHAYA DALAM SISTEM MANAJEMEN KESELAMATAN DAN KESEHATAN KERJA DI PT PERTAMINA TRANS KONTINENTAL SHOREBASE TANJUNG BATU - Yuliana, LINA; Innani taqwaa, Namira (Program Studi Kesehatan dan Keselamatan Kerja, 2022)
The industrial sector can be said to be one of the sectors that contribute to the highest number of work accidents in Indonesia because it has a high risk of work accidents. The purpose of this study was to determine the implementation of the Occupational Health and Safety Management System in reporting hazards in accordance with PP No. 50 of 2012. This study was descriptive with data collection methods in the form of observation and interviews. The implementation of the OHS Management System at PT Pertamina Trans Kontinental Shorebase Tanjung Batu is carried out in an integrated manner in accordance with the ISO 45001 standard, especially in element 8 regarding hazard reporting and improvement of deficiencies. The result of the implementation of hazard reporting is 75%, which is included in the good category. PT Pertamina Trans Kontinental is expected to be more transparent in terms of reporting hazards in the workplace to every worker, so that companies can maximize their efforts to prevent work accidents and occupational diseases. Keywords: Accident; Hazard; Implementation; Management; Reporting;